2022
DOI: 10.1200/jco.2022.40.4_suppl.383
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab plus best supportive care versus placebo plus best supportive care as second-line therapy in patients in Asia with advanced hepatocellular carcinoma (HCC): Phase 3 KEYNOTE-394 study.

Abstract: 383 Background: The anti–PD-1 antibody pembro showed efficacy and manageable safety in the global phase 2 KEYNOTE-224 and phase 3 KEYNOTE-240 studies of patients (pts) with previously treated advanced HCC, a population of high unmet need. KEYNOTE-394 is a randomized, double-blind, phase 3 study conducted in Asia to evaluate the efficacy and safety of pembro vs placebo, both given with BSC, as second-line therapy for previously treated advanced HCC (NCT03062358). Methods: Eligible pts in Asia with confirmed ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 0 publications
4
79
0
1
Order By: Relevance
“…KEYNOTE 394, which had a similar trial design as KEYNOTE 240 but accrued patients exclusively from Asia, was recently presented. 15 The study reported an improvement in OS with pembrolizumab versus placebo of 14.6 months (12.6-18.0) versus 13.0 months (10.5-15.1) with a HR of 0.79 (95% CI, 0.63 to 0.99; P = .018). It improved the PFS from 2.3 months to 2.6 months (HR 0.74; 95% CI, 0.60 to 0.92; P = .0032) and ORRs from 1.3% to 13.7% with a median duration of response of 23.9 months in the pembrolizumab arm.…”
Section: Single-agent Datamentioning
confidence: 95%
“…KEYNOTE 394, which had a similar trial design as KEYNOTE 240 but accrued patients exclusively from Asia, was recently presented. 15 The study reported an improvement in OS with pembrolizumab versus placebo of 14.6 months (12.6-18.0) versus 13.0 months (10.5-15.1) with a HR of 0.79 (95% CI, 0.63 to 0.99; P = .018). It improved the PFS from 2.3 months to 2.6 months (HR 0.74; 95% CI, 0.60 to 0.92; P = .0032) and ORRs from 1.3% to 13.7% with a median duration of response of 23.9 months in the pembrolizumab arm.…”
Section: Single-agent Datamentioning
confidence: 95%
“…Median PFS was 2.6 months for pembrolizumab versus 2.3 months for placebo. The ORR was 13.7% in the pembrolizumab group versus 1.3% in the BSC group, with a median duration of response of 23.9 months versus 5.6 months, “confirming that this agent has a positive effect as monotherapy” [ 14 ].…”
Section: Immune Checkpoint Inhibitor (Ici) Monotherapy In Advanced Hc...mentioning
confidence: 97%
“…The incidence of treatment-related AEs was relatively higher in pembrolizumab arm than that in placebo arm (66.9% vs 49.7%), which was consistent with that in the trial Keynote-224 and Keynote-240. 154 In addition, the post hoc analysis of Keynote-240 revealed that pembrolizumab did not significantly affect liver function in comparison to placebo in aHCC, and exhibited an improved survival regardless of ALBI grade. 155 The HRQOL assessment documented that pembrolizumab could provide a good HRQOL to aHCC patients.…”
Section: Treatment Advances In Systemic Therapymentioning
confidence: 98%